Stable immobilization of uranium in iron containing environments with microbial consortia enriched via two steps accumulation method. (1st February 2022) - Zhu, Yuling; Sheng, Yating; Liu, Yuxin; Chen, Jiemin; He, Xiaoyun; Wang, Wenzhong; Hu, Baowei
Abstract: The stable stabilization of uranium (U) in iron (Fe) containing environments is restricted by the reoxidation of UO2 . In the current study, based on air reoxidation tests, we propose a novel two steps accumulation method to enrich microbial consortia from paddy soil. The constructed microbial consortia, denoted as the Fe–U bacteria, can co-precipitate U and Fe to form stable Fe–U solids. Column experiments running for 4 months demonstrated the production of U(IV)–O–Fe(II) precipitates containing maximum of 39.51% uranium in the presence of Fe–U bacteria. The reoxidation experiments revealed the U(IV)–O–Fe(II) precipitates were more stable than UO2 . 16S rDNA high throughput sequencing analysis demonstrated that Acinetobacter and Stenotrophomonas were responsible for Fe and U precipitation, while, Caulobacteraceae and Aminobacter were crucial for the formation of U(VI)-PO4 chemicals. The proposed two steps accumulation method has an extraordinary application potential in stable immobilization of uranium in iron containing environments. Graphical abstract: Image 1 Highlights: Fe–U bacteria were enriched from soil with a novel "two steps accumulation method". Maximum U content of 39.51% was detected in Fe–U co-precipitates with the bacteria. Fe–U co-precipitates were more stable than UO2 in the presence of O2 . Acinetobacter and Stenotrophomonas were responsible for the Fe–U co-precipitation. Caulobacteraceae and Aminobacter were fundamental to Fe–U–P chemicals formation.